Produção de ferramentais por manufatura aditiva pelo processo de modelagem por deposição fundida - Verissimo, Wellington Bazarim (2024)
Additive Manufacturing (AM) plays an essential role as an alternative to conventional methods, making various production processes possible and enabling customized parts widely used today. In this context, AM is a high-potential technology that can replace conventional tooling processes in metallic and non-metallic materials manufactured by conventional methods. It also offers economic and technical advantages, especially in producing prototypes on an industrial scale. This dissertation presents three articles on applying Additive Manufacturing - Fused Deposition Modeling (FDM) for tooling. The first article presents a systematic literature review (SLR) on using AM in manufacturing tooling, fixtures, and jigs for industrial manufacturing processes. The second article presents a comparative study of the cost, manufacturing time and specific tooling mass produced in ABS-M30, using 3D printing, compared to the conventional machining 6061-T6 aluminum alloy. The third article presents a framework for manufacturing tooling using the high-performance polymer material Polyetherimide (PEI) Ultem 9085. The results of the first article highlight the need to evaluate different types of materials in manufacturing tooling, devices and jigs by Additive Manufacturing compared to conventional methods. This work highlighted the need to validate the technology in industrial segments that still need to be studied, as the selected works show relevance, based on the citations found, generating research opportunities in this specific manufacturing area. The result of the second article compares the Additive Manufacturing method with the conventional method, relating cost, manufacturing time and specific mass. The result of the third article was the validation of a framework for manufacturing tooling in the aeronautical segment using the high-performance polymer Ultem 9085. The framework developed for tooling production proved effective in replacing conventional 6061-T6 aluminum tooling with the Additive Manufacturing - FDM solution. The results indicate that using AM significantly benefits lightness, structural performance, and manufacturing time. However, to guarantee the precision and suitability of the parts produced, the technical requirements of the 3D printing equipment must be fully aligned with the tooling's Geometry and Dimensional Tolerance (GD&T) requirements. This technical alignment between Additive Manufacturing and GD&T is essential to guarantee reliability, repeatability and viability in using Additive Manufacturing solutions in the aeronautical sector and other highly demanding industries.